IMPROVING MATHEMATICS LEARNING OUTCOMES THROUGH LONG BOARD MEDIA FOR CLASS III STUDENTS AT SDN MOJOPITU - Ria Widyaningsih; Agung Setyawan (maktab: Jurnal Pendidikan dan Teknologi, 2022)
This study aims to determine whether the long unit board learning media can improve student learning outcomes at SDN Mojopitu, Slahung sub-district. This research is a classroom action research using Kurt Lewin's research design. In this classroom action research, it was conducted at SDN Mojopitu, Slahung District, Ponorogo Regency by taking the research subject for grade 3 as many as 6 students. Data collection techniques used in this study were interviews, observation, documentation, posttest and pretest. The instruments used in this study include teacher interview texts, posttest and pretest instruments. The results showed that the long unit board learning media could improve students' understanding of the length unit material for grade 3 students at Mojopitu State Elementary School, Slahung District, Ponorogo Regency. It shows that learning the length unit material using the long unit board media that the average class in the initial conditions is 56.66 with a classical mastery level of 33.33%. In the first cycle the average class was 61.66 with 50% classical completeness. Then in the second cycle the class average was 63.33 with 73.33% classical completeness.